Water-non-dispersible composition, cement paste containing same, and preparation method and application of water-non-dispersible composition
By using a water non-dispersible composition composed of microbial polysaccharide polymer compounds, organic polymer compounds and inorganic particles, the problem of strength decay under high temperature conditions is solved, and the stability of cement slurry at high temperature is achieved and The sealing effect ensures effective sealing of high aquifers and leakage layers, and improves cementing quality and oil and gas resource extraction efficiency.
Patent Information
- Application Number
- CN202310764576.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-27
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-06-27
AI Technical Summary
Existing cement slurry can easily cause cementite strength decline under high temperature conditions, and cannot effectively seal the high aquifer and plug the leakage loss layer, resulting in poor cementing quality.
A water-free composition composed of microbial polysaccharide polymer compounds, organic polymer compounds and inorganic particles is prepared by combining G-grade oil well cement, active materials, high-temperature strength stabilizers, etc. , to ensure the non-dispersibility and structural integrity of the cement slurry when exposed to water within room temperature to 180°C.
The stability and rheology of cement slurry under high temperature conditions are achieved, the cement particles are avoided from being flushed by the formation water, the effective sealing of high aquifers and the effective sealing of leakage layers is ensured, and the cementing quality and oil and gas resources are improved. efficiency.
Smart Images

Figure CN119191747A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of well cementing, and in particular to a water-indispersible composition and cement slurry containing the same, as well as a preparation method and application thereof. Background Art
[0002] In the long-term water injection development process, water-driven oil production leads to a complex formation pressure system. In the vertical direction of the formation, there are multiple pressure systems in the same wellbore, especially in complex formations, where mutual crosstalk is easy to occur between layers. If new wells are drilled in these areas, when the cementing cement slurry is replaced and waiting to solidify, the cement slurry structure is easily destroyed by formation water, resulting in water intrusion, channeling and other problems, which seriously affect the cementing quality of the aquifer. In the cementing process, there is a serious loss of cement slurry, which leads to reduced annular displacement efficiency, insufficient cement slurry return depth, resulting in leakage and sealing of the upper well section, and the cementing quality cannot be guaranteed.
[0003] Effective isolation of high-aquifer layers and effective plugging of leakage layers are the key to ensuring the smooth construction of oil and gas wells. During the construction of high-aquifer isolation and leakage layer plugging, when cementing cement slurry is injected into the high-water annulus or leakage layer, the formation water dissolves, migrates and flushes the ordinary cement slurry, and the solid phase structure of the cement slurry is destroyed. It is impossible to effectively isolate the aquifer and plug the leakage layer, which seriously affects the quality and progress of the project. At present, in order to improve the isolation quality of high-aquifer layers and the plugging effect of leakage layers, it is usually necessary to add water-insoluble materials to ordinary cement slurry to prevent the cement slurry particles from being dispersed by formation water during construction. Traditional water-insoluble materials include polyacrylamide polymers and their copolymers, in addition to natural modified polymer compound materials such as cellulose ethers. Although traditional water-insoluble materials and systems have certain water-insoluble properties, they still have the following shortcomings:
[0004] ① Polyacrylamide-based water-indispersible materials work best at temperatures below 80°C, but are prone to decomposition at temperatures above 80°C, and cannot effectively prevent cement slurry particles from being dispersed by water;
[0005] ② Cellulose ether water-indispersible materials have good thickening effect at low temperatures, but will gel at 60-90°C, resulting in poor cement slurry construction performance and prone to cementing accidents such as "sausage filling" and annular blockage;
[0006] ③ Conventional water-non-dispersible cement slurry systems usually do not add high-temperature strength stabilizers, which can easily cause cement stone strength decline under high temperature conditions.
[0007] Therefore, it is necessary to seek a cement slurry that does not disperse in water over a wide temperature range, which can ensure the high aquifer isolation effect and the leakage layer plugging effect at different well depths when isolating high aquifers and plugging leakage layers. Summary of the invention
[0008] The purpose of the present invention is to overcome the problem that cement slurry in the prior art is prone to cause cement stone strength decline under high temperature conditions, and to provide a water-indispersible composition and cement slurry containing the same, as well as a preparation method and application thereof. The cement slurry containing the water-indispersible composition has good water-indispersibility in the temperature range of room temperature to 180°C, can ensure the effective filling of the annular cement slurry and the structural integrity of the cement annulus, and realize the effective isolation of high aquifers at different well depths and the effective plugging of the leakage layer.
[0009] In order to achieve the above object, the present invention provides a water-indispersible composition in a first aspect, comprising: 0.5-5 parts by weight of a microbial polysaccharide polymer compound, 5-50 parts by weight of an organic polymer compound and 4.5-45 parts by weight of inorganic particles.
[0010] The second aspect of the present invention provides use of the aforementioned water-indispersible composition in cement slurry.
[0011] A third aspect of the present invention provides a cement slurry, wherein the cement slurry contains the aforementioned water-indispersible composition.
[0012] A fourth aspect of the present invention provides a method for preparing cement slurry, the method comprising:
[0013] Mixing the G-class oil well cement, the aforementioned water-indispersible composition, active material, high temperature strength stabilizer, density regulator, fluid loss additive, suspension stabilizer and dispersant to obtain a dry mix;
[0014] mixing a retarder, a defoamer and water to obtain a wet mix;
[0015] The dry mix and the wet mix are mixed at a low stirring speed and then stirred at a high speed to obtain cement slurry.
[0016] A fifth aspect of the present invention provides use of the cement slurry of the third aspect or the cement slurry prepared by the preparation method of the fourth aspect in cementing operations of oil and gas wells.
[0017] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:
[0018] (1) The water-indispersible composition of the present invention has good water-indispersibility within the temperature range of room temperature to 180° C., and can be used to prepare cement slurry, which can ensure that the particles in the cement slurry are not dispersed by formation water, and at the same time has no adverse effect on the conventional properties of the cement slurry, such as rheology, water loss, stability, and strength of cement stone.
[0019] (2) The cement slurry of the present invention contains a water-insoluble composition, which has the property that the cement slurry particles are not dispersed when in contact with water, that is, it is non-dispersible in water, which can ensure the effective filling of the annulus with cement slurry and the structural integrity of the cement annulus.
[0020] (3) The cement slurry of the present invention is suitable for high aquifer isolation and leakage zone plugging. It has good non-dispersibility in water within the temperature range of room temperature to 180°C, and can effectively isolate high aquifers at different well depths and effectively plug leakage zones, providing good wellbore conditions for oil and gas production and ensuring efficient exploitation of oil and gas resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is the 90°C thickening curve of Example 2 + 1% retarder;
[0022] Figure 2 is the thickening curve of Example 2 + 1% retarder at 110°C;
[0023] Figure 3 is the 130°C thickening curve of Example 2 + 1% retarder;
[0024] Figure 4 is the static gel strength change curve of Example 2 (180°C×20.7MPa);
[0025] Figure 5 This is a diagram of cement slurry placed in suspension;
[0026] Figure 6 This is a graph to evaluate the non-dispersion performance of cement slurry, where (a) is very poor, (b) is relatively poor, (c) is average, (d) is good, and (e) is very good. DETAILED DESCRIPTION
[0027] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0028] The first aspect of the present invention provides a water-indispersible composition, comprising: 0.5-5 parts by weight of a microbial polysaccharide polymer compound, 5-50 parts by weight of an organic polymer compound, and 4.5-45 parts by weight of inorganic particles.
[0029] Preferably, the water non-dispersible composition comprises: 1-4 parts by weight of a microbial polysaccharide polymer compound, 10-30 parts by weight of an organic polymer compound and 10-30 parts by weight of inorganic particles.
[0030] In the present invention, the water non-dispersible composition refers to a mixture which ensures that the cement slurry particles will not be dispersed by water after being mixed with the cement slurry.
[0031] The water-indispersible composition of the present invention is compounded with microbial polysaccharide polymer compounds, organic polymer compounds and inorganic particles. The characteristics of the microbial polysaccharide polymer compounds, such as high efficiency, non-toxicity, no secondary pollution, self-degradability and wide applicable temperature range, and the flocculation characteristics of the organic polymer compounds are utilized. Through the synergistic effect of the three, the cement slurry particles are wrapped up to prevent the cement slurry particles from being dispersed by formation water when injected into high aquifers and leakage layers. The composition can adapt to different formation temperature conditions and meet the performance requirements of cement slurry for high aquifer isolation and leakage layer plugging operations at different well depths.
[0032] In the present invention, the microbial polysaccharide polymer compound can increase the viscosity of the cement slurry, so that the particulate matter can be evenly suspended in the slurry, and at the same time, it has the characteristics of not decomposing and shearing and thinning under high temperature conditions, and can ensure the stability and rheology of the cement slurry under high temperature conditions. The organic polymer compound can wrap the particulate matter through the organic polymer long chain to form a grid structure with a certain strength to avoid being dispersed by water. The inorganic particles are evenly suspended in the slurry under the action of the microbial polysaccharide polymer compound, and at the same time, by combining with the long chain of the organic high analytical compound, the strength of the grid structure is improved, and the resistance to water impact is enhanced.
[0033] In some embodiments of the present invention, the microbial polysaccharide polymer compound is selected from one or more of xanthan gum, gellan gum, pullulan, trehalose, hyaluronic acid, thermogel, chitosan, curdlan and thermogel.
[0034] In some embodiments of the present invention, the structural skeleton of the microbial polysaccharide polymer compound is connected by chemical bonds of one or more of glucose, glucuronic acid, rhamnose, maltotriose, and acetylglucosamine, and the side chain is connected by chemical bonds of one or more of mannose, rhamnose, and glucuronic acid.
[0035] The microbial polysaccharide macromolecular compound of the present invention has a large number of carboxyl structures and has good hydrophilic properties.
[0036] In some embodiments of the present invention, the organic polymer compound is selected from one or more polymers formed by alkaline hydrolysis of polyethylene oxide, polyvinyl alcohol, polyacrylic acid, sodium polyacrylate, calcium polyacrylate and polyacrylamide; and / or, the organic polymer compound is selected from one or more copolymers formed by styrene sulfonate, wood sulfonate, acrylic acid and methacrylic acid.
[0037] In the present invention, the organic polymer compound is selected from polymers such as polyethylene oxide, polyvinyl alcohol, polyacrylic acid, sodium polyacrylate, calcium polyacrylate, alkaline hydrolyzate of polyacrylamide, and one or more of styrene sulfonate, wood sulfonate, acrylic acid, and methacrylic acid copolymers.
[0038] In the present invention, the microbial polysaccharide polymer compound increases the viscosity of the cement slurry by absorbing water molecules, so that the particulate matter can be evenly suspended in the slurry, and at the same time has the characteristics of not decomposing at high temperature and shear thinning, which can ensure that the cement slurry is stable under high temperature conditions and the rheology meets the cementing requirements; the organic polymer compound has a large number of ether bonds and hydrogen bonds in its molecular structure, which can be combined with inorganic particles, and the particulate matter of other components in the cement slurry can be wrapped up by the long organic polymer chain to form a grid structure with a certain strength, thereby enhancing the resistance to water impact and avoiding being dispersed by water.
[0039] In some embodiments of the present invention, the number average molecular weight of the organic polymer compound is 100,000-1,000,000 g / mol.
[0040] In some embodiments of the present invention, the inorganic particles are acid-washed quartz sand.
[0041] In some embodiments of the present invention, the average particle size of the inorganic particles is 5-75 μm.
[0042] The water-indispersible composition of the present invention is prepared by compounding microbial polysaccharide polymer compounds, organic polymer compounds and inorganic particles. The characteristics of the microbial polysaccharide polymer compounds, such as high efficiency, non-toxicity, no secondary pollution, self-degradability, wide applicable temperature range and shear dilution, can be used to increase the viscosity of the cement slurry, so that the particulate matter can be evenly suspended in the slurry within a wide temperature range, and the slurry can have good rheological properties. The flocculation characteristics of the organic polymer compounds are used to wrap the inorganic particles through high-molecular long chains to form a grid structure with a certain strength. Through the synergistic effect of the three, the cement slurry particles are wrapped to prevent the cement slurry particles from being dispersed by formation water when injected into high-aquifer layers and leakage layers. The composition can adapt to different formation temperature conditions and meet the performance requirements of cement slurry for high-aquifer isolation and leakage layer plugging operations at different well depths.
[0043] The second aspect of the present invention provides use of the aforementioned water-indispersible composition in cement slurry.
[0044] A third aspect of the present invention provides a cement slurry, wherein the cement slurry contains the aforementioned water-indispersible composition.
[0045] The cement slurry of the present invention contains a water-indispersible composition, and has the characteristic that the cement slurry particles are not dispersed when in contact with water, that is, it is non-dispersible in water, and can ensure the effective filling of the annulus cement slurry and the structural integrity of the cement annulus.
[0046] In some embodiments of the present invention, the cement slurry comprises: 100 parts of G-grade oil well cement, 0.5-2 parts of the water-indispersible composition, 1-3 parts of active materials, 0-50 parts of high temperature strength stabilizer, 0-100 parts of density regulator, 2-5 parts of fluid loss reducer, 0.2-2 parts of suspension stabilizer, 1-3 parts of dispersant, 0.1-2.5 parts of retarder, 0.1-0.5 parts of defoamer and 40-110 parts of water.
[0047] In the present invention, it is found through research that the amount of water-indispersible composition added cannot be too little, less than 0.5 parts, the water-indispersible composition cannot effectively wrap up other components in the cement slurry, resulting in poor water-indispersibility of the cement slurry, and it is easy to be washed away by water when in contact with formation water; the amount of water-indispersible composition added cannot be too much, more than 2 parts, the rheology of the cement slurry deteriorates, the consistency is high, and it is difficult for cement trucks to replace cement slurry during cementing. The present invention selects a suitable water-indispersible composition and controls its addition amount to wrap up other components in the cement slurry, so as to avoid the cement slurry components being washed away by formation water when being replaced in high aquifers and leakage layers, and can adapt to different formation temperature conditions, and meet the performance requirements of cement slurry for high aquifer isolation and leakage layer plugging operations at different well depths.
[0048] In the present invention, when the ambient temperature is low, there is no problem of high-temperature decay in strength, so the amount of high-temperature strength stabilizer added can be zero at this time; when the cement slurry density is the conventional density of 1.90, the density regulator can be zero, which can ensure that the cement slurry density is around the conventional density of 1.90.
[0049] Preferably, the cement slurry comprises: 100 parts of G-grade oil well cement, 0.8-1.5 parts of the water-indispersible composition, 1.5-2.5 parts of active materials, 10-40 parts of high temperature strength stabilizer, 20-80 parts of density regulator, 3-4 parts of fluid loss reducer, 0.5-1.5 parts of suspension stabilizer, 1.5-2.5 parts of dispersant, 0.5-2 parts of retarder, 0.2-0.4 parts of defoamer and 50-100 parts of water.
[0050] In some embodiments of the present invention, the active material is active microsilicon, and the average particle size thereof is 0.1-0.5 μm.
[0051] In the present invention, the active material can improve the consistency of cement slurry, help the cement slurry to achieve non-dispersibility when encountering water, and enhance the strength of the cement slurry under different temperature conditions.
[0052] In some embodiments of the present invention, the high temperature strength stabilizer is acid-washed quartz sand, the SiO2 content of which is greater than 99% and the average particle size of which is 5-75 μm.
[0053] In the present invention, the high temperature strength stabilizer can reduce the Ca(OH)2 content and the calcium-silicon ratio (C / S) in the cement paste, and prevent the strength of the cement paste from declining under high temperature conditions.
[0054] In some embodiments of the present invention, the density regulator includes a weighting material and a lightening material; wherein the weighting material is selected from one or more of iron ore powder, barite and micro-manganese ore powder; and the lightening material is selected from one or more of glass microbeads, floating beads and fly ash.
[0055] In the present invention, the weighting material and the lightening material are used as density regulators, and the density of the cement slurry system is adjusted by utilizing the density characteristics thereof to meet the requirements of different working conditions for the density of the cement slurry system.
[0056] Other admixtures used in the present invention, such as suspension stabilizers, retarders, dispersants, and defoamers, are all commonly used admixtures in the art. The relevant mechanisms and properties are well known to those skilled in the art and will not be described in detail here.
[0057] In some embodiments of the present invention, the retarder is selected from one or more of AMPS substances and organophosphate substances.
[0058] In some embodiments of the present invention, the fluid loss reducer is selected from one or more of AMPS, polymers formed by polymerization of low molecular weight amides and polyhydroxycarboxylic acid substances, and PVA substances.
[0059] In the present invention, the polymer is formed by polymerizing AMPS, low molecular weight amide and polyhydroxycarboxylic acid substances, and the fluid loss reducer is selected from one or more of the polymer and PVA substances.
[0060] In some embodiments of the present invention, the suspension stabilizer is selected from plant gum polymer compounds or cellulose polymer compounds.
[0061] Preferably, the plant gum polymer compound is selected from one or more of guar gum, curdlan, carrageenan and acacia gum.
[0062] Preferably, the cellulose polymer compound is selected from one or more of lignin fiber, cellulose ether, methyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose and carboxymethyl cellulose.
[0063] In some embodiments of the present invention, the dispersant is selected from one or more of a condensation product of formaldehyde and acetone, polystyrene sulfonates and polycarboxylates.
[0064] Preferably, the dispersant is selected from one or two of a condensation product of formaldehyde and acetone, a polystyrene sulfonate dispersant and a polycarboxylic acid dispersant.
[0065] In some embodiments of the present invention, the defoaming agent is selected from one or more of tributyl phosphate, polyoxypropylene glycerol and polydimethylsiloxane.
[0066] In some embodiments of the present invention, the density of the cement slurry is 1.2-2.4 g / cm 3 , the applicable temperature range is 10-180℃.
[0067] In some embodiments of the present invention, the fluidity of the cement slurry is greater than 22 cm, the API water loss is less than 50 mL, and the free liquid is 0.
[0068] In some embodiments of the present invention, the density is 1.2 g / cm 3 The cement slurry does not disperse when it comes into contact with water, and its 24h compressive strength is greater than 10MPa.
[0069] In some embodiments of the present invention, the density is 1.9 g / cm 3 The cement slurry does not disperse when it comes into contact with water, and its 24h compressive strength is greater than 20MPa.
[0070] In some embodiments of the present invention, the density is 2.4 g / cm 3 The cement slurry does not disperse when it comes into contact with water, and its 24h compressive strength is greater than 14MPa.
[0071] A fourth aspect of the present invention provides a method for preparing cement slurry, the method comprising:
[0072] Mixing the G-class oil well cement, the aforementioned water-indispersible composition, active material, high temperature strength stabilizer, density regulator, fluid loss additive, suspension stabilizer and dispersant to obtain a dry mix;
[0073] mixing a retarder, a defoamer and water to obtain a wet mix;
[0074] The dry mix and the wet mix are mixed at a low stirring speed and then stirred at a high speed to obtain cement slurry.
[0075] Specifically, the low stirring rate is 4000±200 r / min, the high-speed stirring rate is 12000±500 r / min, the stirring time is 30-40 s, preferably 35 s, and the obtained cement slurry is a cement slurry that does not disperse in water in a wide temperature range.
[0076] The cement slurry of the present invention has an adjustable density (1.2-2.4 g / cm 3 ), has a wide applicable temperature range (room temperature to 180°C), high compressive strength, and a good linear relationship between thickening time and temperature, density, and retarder dosage.
[0077] A fifth aspect of the present invention provides the use of the cement slurry of the third aspect or the cement slurry prepared by the preparation method of the fourth aspect in the isolation of aquifers and plugging of leakage zones in oil and gas wells.
[0078] The cement slurry of the present invention is suitable for high aquifer isolation and leakage layer plugging, and has good non-dispersibility when in contact with water within the temperature range of room temperature to 180°C, thereby achieving effective isolation of high aquifers at different well depths and effective plugging of leakage layers, providing good wellbore conditions for oil and gas production and ensuring efficient exploitation of oil and gas resources.
[0079] The wide temperature range of the present invention does not disperse in water and the density of the cement slurry is adjustable (1.20-2.40g / cm 3 ), applicable temperature range is room temperature - 180 ℃, thickening time has good linear relationship with temperature, density, retarder dosage, fluidity is greater than 22cm, API water loss is less than 50mL, free liquid is 0, 1.2g / cm 3 The 24h compressive strength of the low-density, water-insoluble cement slurry system is greater than 10MPa, 1.9g / cm 3 The 24h compressive strength of the conventional density non-dispersible cement slurry system is greater than 20MPa, 2.4g / cm 3 The 24h compressive strength of the high-density, water-insoluble cement slurry system is greater than 14MPa. The cement slurry has good stability under different temperature conditions; in the process of cementing high-water-content formations and plugging lost-water layers, the cement slurry has good construction performance, and the cement slurry particles are not easily dispersed by formation water during construction, ensuring effective filling of the annulus and integrity of the cement slurry structure, achieving effective isolation of high-water-content annulus layers and effective plugging of lost-water layers; it is of great significance to improve the cementing effect of complex formations and save well construction costs.
[0080] The technical solutions in the present invention are described clearly and completely by way of embodiments below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0081] In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be obtained through commercial channels.
[0082] According to the national standard GB / T 19139-2012 "Test Methods for Oil Well Cement", the experiment was carried out to evaluate the thickening performance, fluidity, API water loss, free water, stability and compressive strength of cement slurry. The main experimental instruments are: 30-60 type wall edge mixer, 8240 type high temperature and high pressure thickener, products of CHANDLER Company of the United States; 4265-HT type high temperature and high pressure static gel strength measuring instrument, products of CHANDLER Company of the United States; HH-420 type constant temperature digital display water tank, Changzhou Yineng Experimental Instrument Factory.
[0083] In the following examples,
[0084] The microbial polysaccharide polymer compound is xanthan gum, produced by Sichuan Kaier Oil and Gas Field Technology Service Co., Ltd.
[0085] The model of the organic polymer compound is polyethylene oxide with a number average molecular weight of 200,000 g / mol, produced by Shandong Wangtong Chemical Co., Ltd.
[0086] The inorganic particle model is DRB-2S, produced by China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.
[0087] G-grade oil well cement is high sulfate resistance (HSR) G-grade oil well cement, produced by Jiahua Special Cement Co., Ltd.
[0088] The model of high temperature strength stabilizer is DRB-2S, produced by China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.
[0089] The density regulator is glass microspheres (12000Psi) produced by China Steel Group Maanshan Mining Institute New Materials Technology Co., Ltd., and refined iron ore powder (6.05g / cm 3 ) is produced by Sichuan Kaier Oil and Gas Field Technology Service Co., Ltd.
[0090] The model of the fluid loss additive is DRF-1S, produced by China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.
[0091] The model of the suspension stabilizer is DRK-3S, produced by China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.
[0092] The model of the dispersant is DRS-1S, produced by China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.
[0093] The model of the retarder is DRH-1L or DRH-2L, produced by China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.
[0094] The model of the defoaming agent is DRX-1L or DRX-2L, produced by China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.
[0095] The water used in the experiment was distilled water.
[0096] The method for evaluating the non-dispersibility of cement slurry when in contact with water before curing has the following specific operation procedures: prepare two beakers with a volume of 250 mL, pour 200 mL of distilled water or formation water at room temperature (numbered 1-1#) into one beaker, and pour distilled water or formation water (numbered 1-2#) heated to a set temperature (maximum 100°C) into the other beaker, and perform insulation treatment on the two beakers respectively to ensure that the temperature of the water in the two beakers is at a constant temperature. Prepare about 600 mL of non-dispersible cement slurry when in contact with water according to the preparation method described in claim 10, pour it into two beakers with a volume of 50 mL (numbered 1-1-1# and 1-2-2#, respectively), let it stand for a certain time (recommended 10 minutes), and then suspend the 1-1-1# and 1-2-2# beakers at a certain height (recommended 1 cm, such as 1 cm) above the 1-1# and 1-2# beakers, respectively. Figure 5 Then pour the cement slurry into beakers 1-1# and 1-2# at a certain flow rate (recommended 2mL / s). According to whether the poured cement slurry can be dispersed by water and the turbidity of the water on the top of beakers 1-1# and 1-2#, set the water non-dispersion performance to 5 levels, such as Figure 6 As shown, the water non-dispersibility of cement slurry is evaluated by this method. The present invention evaluates the non-dispersibility according to the clarity of the upper liquid, with a total of 5 levels from very clear to very turbid. Figure 6 The ratings are as follows: (a) very good, (b) good, (c) fair, (d) poor, and (e) very poor.
[0097] The evaluation method of the non-dispersibility of cement slurry in contact with water after curing is as follows: prepare two beakers with a volume of 250 mL, pour 200 mL of distilled water or formation water at room temperature (numbered 2-1#) into one beaker, and pour distilled water or formation water (numbered 2-2#) heated to a set temperature (maximum 100°C) into the other beaker, and perform insulation treatment on the two beakers respectively to ensure that the temperature of the water in the two beakers is at a constant temperature, and then prepare about 600 mL of non-dispersible cement slurry in contact with water according to the preparation method of claim 10, set the curing temperature and pressure as needed, and perform curing for a certain period of time. After the curing is completed, pour the water into two beakers with a volume of 50 mL (numbered 2-1-1# and 2-2-2#, respectively) and let it stand for a certain period of time (recommended 10 minutes), and then suspend the 2-1-1# and 2-2-2# beakers at a certain height (recommended 1 cm, such as 2-1# and 2-2#) above the 2-1# and 2-2# beakers, respectively. Figure 5 Then pour the cement slurry into 2-1# and 2-2# beakers at a certain flow rate (recommended 2mL / s). According to whether the poured cement slurry can be dispersed by water and the turbidity of the water on the top of 2-1# and 2-2# beakers, set the water non-dispersion performance to 5 levels, such as Figure 6As shown, this is used to evaluate the water non-dispersibility of cement slurry.
[0098] Preparation Example 1
[0099] 2.5 parts by weight of a microbial polysaccharide polymer compound, 30 parts by weight of an organic polymer compound and 45 parts by weight of inorganic particles were sequentially placed in a mixing device and mixed evenly to obtain a water-indispersible composition A1.
[0100] Preparation Example 2
[0101] 0.5 parts by weight of a microbial polysaccharide polymer compound, 10 parts by weight of an organic polymer compound and 25 parts by weight of inorganic particles were sequentially placed into a mixing device and mixed evenly to obtain a water-indispersible composition A2.
[0102] Preparation Example 3
[0103] 5 parts by weight of a microbial polysaccharide polymer compound, 50 parts by weight of an organic polymer compound and 20 parts by weight of inorganic particles are sequentially placed in a mixing device and mixed evenly to obtain a water-indispersible composition A3.
[0104] Preparation Comparative Example 1
[0105] 30 parts by weight of an organic polymer compound and 45 parts by weight of inorganic particles were sequentially placed in a mixing device and mixed evenly to obtain a water-indispersible composition D1.
[0106] Preparation Comparative Example 2
[0107] 2.5 parts by weight of a microbial polysaccharide polymer compound and 45 parts by weight of inorganic particles were sequentially placed in a mixing device and mixed evenly to obtain a water-indispersible composition D2.
[0108] Preparation Comparative Example 3
[0109] 2.5 parts by weight of a microbial polysaccharide polymer compound and 30 parts by weight of an organic polymer compound were sequentially placed in a mixing device and mixed evenly to obtain a water-indispersible composition D3.
[0110] Example 1
[0111] The cement slurry formula includes the following components by weight: 100 parts of G-grade oil well cement, 1 part of water-indispersible composition A1, 61 parts of density regulator (0.62 g / cm 3 glass microspheres), 2 parts of active microsilica, 30 parts of high temperature strength stabilizer, 1 part of suspension stabilizer, 0.7 parts of retarder, 4.5 parts of fluid loss additive, 2 parts of dispersant, 0.25 parts of retarder, 0.2 parts of defoamer and 103 parts of water, the cement slurry density is 1.2g / cm 3 The test results of conventional properties and non-dispersibility in water are shown in Table 1.
[0112] Example 2
[0113] The cement slurry formula includes the following components in parts by weight: 100 parts of G-grade oil well cement, 1 part of water-indispersible composition A2, 35 parts of high temperature strength stabilizer, 1 part of active microsilica, 0.3 parts of suspension stabilizer, 0.7 parts of retarder, 3.5 parts of fluid loss additive, 2.5 parts of dispersant, 0.2 parts of defoamer and 58 parts of water, and the cement slurry density is 1.9 g / cm 3 The results of the conventional properties and water-resistant properties tests are shown in Table 1, and the results of the thickening time under different retarder dosages are shown in Table 2.
[0114] like Figure 1-3 The thickening curves of the formulation of Example 2 at 90°C, 110°C and 130°C and 60MPa are shown respectively. Figure 1-3 It can be seen that there is no obvious abnormal phenomenon such as bulging in the thickening curve. The thickening time of cement slurry at the three temperature points is 725min, 474min and 174min respectively, indicating that the thickening time changes linearly with the increase of temperature.
[0115] like Figure 4 The static gel strength curve of the formula of Example 2 at 180°C and 20.7MPa is shown. Figure 4 It can be seen that the formulation of Example 2 begins to develop strength in about 4 hours and exceeds 20 MPa in about 10 hours, and then the strength increases slowly and remains above 20 MPa within 168 hours.
[0116] Example 3
[0117] The cement slurry formula includes the following components by weight: 100 parts of G-grade oil well cement, 2 parts of water-indispersible composition A3, 92 parts of density regulator (6.05 g / cm 3 Iron ore powder), 50 parts high temperature strength stabilizer, 1.6 parts suspension stabilizer, 3.2 parts retarder, 3.5 parts fluid loss reducer, 1.5 parts dispersant, 0.2 parts defoamer, 68 parts water, cement slurry density is 2.4g / cm 3 The test results of conventional properties and non-dispersibility in water are shown in Table 1.
[0118] Comparative Example 1
[0119] The cement slurry formula includes the following components by weight: 100 parts of G-grade oil well cement, 61 parts of density modifier (0.62 g / cm 3 glass microspheres), 2 parts of active microsilica, 30 parts of high temperature strength stabilizer, 1 part of suspension stabilizer, 0.7 parts of retarder, 4.5 parts of fluid loss additive, 2 parts of dispersant, 0.25 parts of retarder, 0.2 parts of defoamer and 103 parts of water, the cement slurry density is 1.2g / cm 3The test results of conventional properties and non-dispersibility in water are shown in Table 1.
[0120] Comparative Example 2
[0121] The cement slurry formula includes the following components by weight: 100 parts of G-grade oil well cement, 35 parts of high temperature strength stabilizer, 1 part of active microsilica, 0.3 parts of suspension stabilizer, 0.7 parts of retarder, 3.5 parts of fluid loss additive, 2.5 parts of dispersant, 0.2 parts of defoamer and 58 parts of water. The cement slurry density is 1.9 g / cm 3 The test results of conventional properties and non-dispersibility in water are shown in Table 1.
[0122] Comparative Example 3
[0123] The cement slurry formula includes the following components by weight: 100 parts of G-grade oil well cement, 92 parts of density modifier (6.05 g / cm 3 Iron ore powder), 50 parts of high temperature strength stabilizer, 1.6 parts of suspension stabilizer, 3.2 parts of retarder, 3.5 parts of fluid loss reducer, 1.5 parts of dispersant, 0.2 parts of defoamer and 68 parts of water, the cement slurry density is 2.4g / cm 3 The experimental results of conventional properties and non-dispersibility in water are shown in Table 1.
[0124] Comparative Example 4
[0125] The cement slurry formula includes the following components by weight: 100 parts of G-grade oil well cement, 1 part of water non-dispersible composition D1, 61 parts of density regulator (0.62 g / cm 3 glass microspheres), 2 parts of active microsilica, 30 parts of high temperature strength stabilizer, 1 part of suspension stabilizer, 0.7 parts of retarder, 4.5 parts of fluid loss additive, 2 parts of dispersant, 0.25 parts of retarder, 0.2 parts of defoamer and 103 parts of water, the cement slurry density is 1.2g / cm 3 The test results of conventional properties and non-dispersibility in water are shown in Table 1.
[0126] Comparative Example 5
[0127] The cement slurry formula includes the following components by weight: 100 parts of G-grade oil well cement, 1 part of water non-dispersible composition D2, 61 parts of density regulator (0.62 g / cm 3 glass microspheres), 2 parts of active microsilica, 30 parts of high temperature strength stabilizer, 1 part of suspension stabilizer, 0.7 parts of retarder, 4.5 parts of fluid loss additive, 2 parts of dispersant, 0.25 parts of retarder, 0.2 parts of defoamer and 103 parts of water, the cement slurry density is 1.2g / cm 3 The test results of conventional properties and non-dispersibility in water are shown in Table 1.
[0128] Comparative Example 6
[0129] The cement slurry formula includes the following components by weight: 100 parts of G-grade oil well cement, 1 part of water non-dispersible composition D3, 61 parts of density regulator (0.62 g / cm 3 glass microspheres), 2 parts of active microsilica, 30 parts of high temperature strength stabilizer, 1 part of suspension stabilizer, 0.7 parts of retarder, 4.5 parts of fluid loss additive, 2 parts of dispersant, 0.25 parts of retarder, 0.2 parts of defoamer and 103 parts of water, the cement slurry density is 1.2g / cm 3 The test results of conventional properties and non-dispersibility in water are shown in Table 1.
[0130] Table 1 Comparison of performance of cement slurry systems with different densities that do not disperse in water
[0131]
[0132] Table 1 Comparison of performance of cement slurry systems with different densities that do not disperse in water (continued)
[0133]
[0134] Table 2 Thickening time of cement slurry under different retarder dosages in Example 2
[0135]
[0136] It can be seen from the data in Table 1 that a wide temperature range water-independent cement slurry system can show good water-independent properties when in contact with room temperature water and 100°C water before and after high temperature and high pressure curing. At the same time, the fluidity of all embodiments is greater than 22 cm, the API water loss is less than 50 mL, the free water content is 0, and the stability is less than 0.02 g / cm 3 .
[0137] Under the same experimental conditions, the fluidity, API water loss, free water, stability and other data of Example 1, Example 2 and Example 3 are not much different from those of Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5 and Comparative Example 6, indicating that the water-insoluble composition has no adverse effect on the conventional properties of cement slurry.
[0138] The experimental temperatures of Example 1, Comparative Example 1, Comparative Example 4, Comparative Example 5 and Comparative Example 6 were all 90°C, and the thickening times were 235 min, 224 min, 239 min, 243 min and 247 min, respectively. The experimental temperatures of Comparative Example 2 and Example 2 were all 110°C, and the thickening times were 291 min and 312 min, respectively. The experimental temperatures of Comparative Example 3 and Example 3 were all 150°C, and the thickening times were 201 min and 213 min, respectively. It can be seen that the water-insoluble composition has no adverse effect on the thickening time of the cement slurry.
[0139] The compressive strengths of Comparative Example 1 and Example 1 after curing for 24 hours at 110°C and 20.7 MPa are 11.9 MPa and 11.5 MPa, respectively; the compressive strengths of Comparative Example 2 and Example 2 after curing for 24 hours at 130°C and 20.7 MPa are 22.1 MPa and 20.25 MPa, respectively; the compressive strengths of Comparative Example 3 and Example 3 after curing for 24 hours at 180°C and 20.7 MPa are 18.4 MPa and 16.5 MPa, respectively. It can be seen that the water-indispersible composition has no adverse effect on the strength of cement paste.
[0140] The cement slurry density of Example 1 is 1.20 g / cm 3 , 24h compressive strength is greater than 10MPa; the cement slurry density of Example 2 is 1.90g / cm 3 , 24h compressive strength is greater than 20MPa; the cement slurry density of Example 3 is 2.40g / cm 3 , the 24h compressive strength is greater than 14MPa. It can be seen that the strength of the cement slurry system that does not disperse when exposed to water meets the requirements of cementing construction.
[0141] Comparative Example 1 does not contain any water-based non-dispersible composition, while Example 1 contains 1 portion of water-based non-dispersible composition. Compared with Comparative Example 1, Example 1 is poured into room temperature water and 100°C water before and after high temperature and high pressure curing, and the cement slurry has good water non-dispersibility. It can be seen that Example 1 has good water non-dispersibility.
[0142] Comparative Example 2 does not add water to the non-dispersible composition, and Example 2 is 1 part of the non-dispersible composition. Compared with Comparative Example 2, Example 2 is poured into room temperature water and 100°C water before and after high temperature and high pressure curing, and the cement slurry has good non-dispersibility when it comes into contact with water. It can be seen that Example 2 has good non-dispersibility when it comes into contact with water.
[0143] Comparative Example 3 does not add water to the non-dispersible composition, and Example 3 is 2 parts of the non-dispersible composition. Compared with Comparative Example 3, Example 3 is poured into room temperature water and 100°C water before and after high temperature and high pressure curing, and the cement slurry water non-dispersibility is good, which shows that Example 3 has good water non-dispersibility.
[0144] Comparative Example 4 does not add water to the microbial polysaccharide polymer compound in the non-dispersible composition, and Example 1 is 1 part of the non-dispersible composition in water. Compared with Example 1, Comparative Example 4 was poured into room temperature water and 100°C water respectively before high temperature and high pressure curing, and the cement slurry had good and general non-dispersibility when it came into contact with water. After high temperature and high pressure curing, it was poured into room temperature water and 100°C water respectively, and the cement slurry had general non-dispersibility when it came into contact with water. Comparative Example 5 did not add water to the organic polymer compound in the non-dispersible composition, and Example 1 was 1 part of the non-dispersible composition in water. Compared with Example 1, Comparative Example 5 was poured into room temperature water and 100°C water respectively before high temperature and high pressure curing, and the cement slurry had very good and good non-dispersibility when it came into contact with water. After high temperature and high pressure curing, it was poured into room temperature water and 100°C water respectively, and the cement slurry had good and general non-dispersibility when it came into contact with water. Comparative Example 6 did not add water to the inorganic particles in the non-dispersible composition, and Example 1 was 1 part of the non-dispersible composition in water. Compared with Example 1, the cement slurry of Comparative Example 6 was poured into room temperature water and 100°C water respectively before high temperature and high pressure curing, and the non-dispersibility of the cement slurry in water was very good and good. After high temperature and high pressure curing, the cement slurry was poured into room temperature water and 100°C water respectively, and the non-dispersibility of the cement slurry in water was good, but its 24h strength was poor. It can be seen that the cement slurry can only have good water non-dispersibility when the microbial polysaccharide polymer compound, organic polymer compound and inorganic particles in the water non-dispersible composition act simultaneously.
[0145] From the data in Table 2, it can be seen that the thickening time of Example 2 is adjustable, the thickening curve is normal, and there is no abnormal phenomenon such as "bulging". For Example 2, when the retarder is 0.7 parts, the thickening time under the conditions of 90℃, 110℃, 130℃ and 60MPa pressure is 432min, 312min, 145min respectively; when the retarder is 1.0 parts, the thickening time under the conditions of 90℃, 110℃, 130℃ and 60MPa pressure is 725min, 474min, 174min respectively; when the retarder is 1.5 parts, the thickening time under the conditions of 150℃ and 60MPa pressure is 115min; when the retarder is 2.0 parts, the thickening time under the conditions of 150℃ and 60MPa pressure is 355min. It can be seen that the thickening time of the water-insoluble cement slurry system shows a good linear relationship with the amount of retarder and temperature.
[0146] Therefore, the wide temperature range water-insoluble cement slurry system provided by the present invention can ensure that the cement slurry particles are not dispersed by water when in contact with water, and is suitable for cementing high aquifers and plugging lost layers at static temperatures ranging from room temperature to 180°C, and has no adverse effect on conventional properties such as cement slurry rheology, water loss, stability, and cement stone strength. 3 The 24h compressive strength of the low-density, water-insoluble cement slurry system is greater than 10MPa, 1.9g / cm 3The 24h compressive strength of the conventional density non-dispersible cement slurry system is greater than 20MPa, 2.4g / cm 3 The 24h compressive strength of the high-density, water-insoluble cement slurry system is greater than 14MPa, and the strength data meets the requirements of cementing construction. At the same time, it can ensure the rheological properties of the cement slurry, the thixotropy of the cement slurry is small, and the "bulge" and "step" of the thickening curve are avoided; the thickening time of the cement slurry system has a good linear relationship with the temperature, density, and amount of retarder material; it can achieve effective filling of the annulus, ensure the structural integrity of the cement annulus, improve the sealing effect of the high aquifer and the leakage layer under different temperature conditions, provide good wellbore conditions for oil and gas production, and ensure the efficient exploitation of oil and gas resources.
[0147] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A water-insoluble composition, characterized in that: The water non-dispersible composition comprises: 0.5-5 parts by weight of a microbial polysaccharide macromolecular compound, 5-50 parts by weight of an organic macromolecular compound and 4.5-45 parts by weight of inorganic particles.
2. The water-insoluble composition according to claim 1, wherein The microbial polysaccharide polymer compound is selected from one or more of xanthan gum, gellan gum, pullulan, trehalose, hyaluronic acid, thermogel, chitosan, curdlan and thermogel.
3. The water-insoluble composition according to claim 2, wherein: The structural skeleton of the microbial polysaccharide polymer compound is connected by one or more of glucose, glucuronic acid, rhamnose, maltotriose and acetylglucosamine through chemical bonds, and the side chain is connected by one or more of mannose, rhamnose and glucuronic acid through chemical bonds.
4. The water non-dispersible composition according to claim 1 or 2, wherein The organic polymer compound is selected from one or more of polyethylene oxide, polyvinyl alcohol, polyacrylic acid, sodium polyacrylate, calcium polyacrylate and a polymer formed by alkaline hydrolysis of polyacrylamide; And / or, the organic polymer compound is selected from one or more of styrene sulfonate, wood sulfonate, and copolymers formed by acrylic acid and methacrylic acid; And / or, the number average molecular weight of the organic polymer compound is 100,000-1,000,000 g / mol.
5. The water-insoluble composition according to claim 1 or 2, wherein: The inorganic particles are acid-washed quartz sand; And / or, the average particle size of the inorganic particles is 5-75 μm.
6. Use of the water-indispersible composition according to any one of claims 1 to 5 in cement slurry.
7. A cement slurry, characterized in that: The cement slurry contains the water non-dispersible composition according to any one of claims 1-5.
8. The cement slurry according to claim 7, wherein: The cement slurry comprises: 100 parts of G-grade oil well cement, 0.5-2 parts of the water-indispersible composition, 1-3 parts of active materials, 0-35 parts of high-temperature strength stabilizer, 0-100 parts of density regulator, 2-5 parts of fluid loss reducer, 0.2-0.5 parts of suspension stabilizer, 1-3 parts of dispersant, 0.1-2.5 parts of retarder, 0.1-0.5 parts of defoamer and 40-110 parts of water.
9. The cement slurry according to claim 7 or 8, wherein: The active material is active microsilicon, and the average particle size thereof is 0.1-0.5 μm.
10. The cement slurry according to claim 7 or 8, wherein: The high temperature strength stabilizer is acid washed quartz sand, the SiO2 content of which is greater than 99% and the average particle size of which is 5-75 μm.
11. The cement slurry according to claim 7 or 8, wherein: The density regulator includes a weighting material and a lightening material; wherein the weighting material is selected from one or more of iron ore powder, barite and micro-manganese ore powder; and the lightening material is selected from one or more of glass microbeads, floating beads and fly ash.
12. The cement slurry according to claim 7 or 8, wherein: The retarder is selected from one or more of AMPS substances and organophosphate substances; And / or, the fluid loss reducer is selected from one or more of polymers formed by polymerization of AMPS, low molecular weight amides and polyhydroxycarboxylic acid substances and PVA substances; And / or, the suspension stabilizer is selected from plant gum polymer compounds or cellulose polymer compounds; and / or, the dispersant is selected from one or more of a condensation product of formaldehyde and acetone, polystyrene sulfonates and polycarboxylates; And / or, the defoaming agent is selected from one or more of tributyl phosphate, polyoxypropylene glycerol and polydimethylsiloxane.
13. The cement slurry according to claim 12, wherein: The plant gum polymer compound is selected from one or more of guar gum, curdlan, carrageenan and acacia gum; The cellulose polymer compound is selected from one or more of lignin fiber, cellulose ether, methyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose and carboxymethyl cellulose.
14. The cement slurry according to claim 7 or 8, wherein: The density of the cement slurry is 1.2-2.4 g / cm 3 ; And / or, the use temperature range of the cement slurry is 10-180°C; And / or, the fluidity of the cement slurry is greater than 22 cm, the API water loss is less than 50 mL, and the free liquid is 0.
15. The cement slurry according to claim 7 or 8, wherein: Density: 1.2g / cm 3 The cement slurry does not disperse when it comes into contact with water, and its 24h compressive strength is greater than 10MPa; and / or, density 1.9 g / cm 3 The cement slurry does not disperse when it comes into contact with water, and its 24h compressive strength is greater than 20MPa; and / or, density 2.4 g / cm 3 The cement slurry does not disperse when it comes into contact with water, and its 24h compressive strength is greater than 14MPa.
16. A method for preparing cement slurry, characterized in that: The preparation method comprises: Mixing the G-class oil well cement, the water-indispersible composition according to any one of claims 1 to 5, an active material, a high temperature strength stabilizer, a density regulator, a fluid loss additive, a suspension stabilizer and a dispersant to obtain a dry mix; mixing a retarder, a defoamer and water to obtain a wet mix; The dry mix and the wet mix are mixed at a low stirring speed and then stirred at a high speed to obtain cement slurry.
17. Use of the cement slurry according to any one of claims 7 to 15 or the cement slurry prepared by the preparation method according to claim 16 in the isolation of aquifers and plugging of lost circulation zones in oil and gas wells.
Citation Information
Patent Citations
Elastic-plastic minimum inflation well cement slurry and preparation method thereof
CN105255463A
Ultrahigh-strength tough cement paste system for well cementation as well as preparation and application thereof
CN112939527A
Large-temperature-difference well cementation cement paste and preparation method thereof
CN114380540A
Underwater non-dispersible cement paste for well drilling leakage stoppage as well as preparation method and application of underwater non-dispersible cement paste
CN115893921A
Polymer dispersant for well cementing
US20230151260A1
